THE POLICY BASE AND THE STRENGTHENING OF CHARACTER EDUCATION IN ELEMENTARY SCHOOLS - Eddy Setyanto,; Sulhan, Muhammad; Miranti, Ira; Sanny, Isthifa (International Journal of Psychosocial Rehabilitation, 2020)
This research aims at analyzing the policy base of character education in elementary schools. The policy base applied by governmen is a system that must be run in line with the legal order. This present research is qualitative descriptive research with library research data collection. The policy base and the strengthening of character education since elementary school are essential factors for success at the next level. It was integrating knowledge on the curriculum and on the teaching-learning process, which is appropriate to the environment. Education must be comprehended as a process of creating humans as a whole and humane for being the right person that is suited to norms and too noble values that exist in society. This cannot be missed from the visions and mission of the school as an educational institution. The process that can be done is by integrating the cultural wisdom of the local environment. Therefore, the output is a school as an educational institution, that the school does create its graduates to have the technical skill and not only academic, but also highly values the cultural moral and the community’s local wisdom as Indonesian national identity